Evaluating the impact of the national health insurance scheme of Ghana on out of pocket expenditures: a systematic review - Juliet Okoroh; Samuel Essoun; Anthony Seddoh; Hobart Harris; Joel S. Weissman; Lydia Dsane-Selby; Robert Riviello (BMC, 2018)
Abstract Background Approximately 150 million people suffer from financial catastrophe annually because of out-of-pocket expenditures (OOPEs) on health. Although the National Health Insurance Scheme (NHIS) of Ghana was designed to promote universal health coverage, OOPEs as a proportion of total health expenditures remains elevated at 26%, exceeding the WHO's recommendations of less than 15-20%. To determine whether enrollment in the NHIS reduces the likelihood of OOPEs and catastrophic health expenditures (CHEs) in Ghana, we undertook a systematic review of the published literature. Methods We searched for quantitative articles published in English between January 1, 2003 and August 22, 2017 in PubMed, Google Scholar, Economic Literature, Global Health, PAIS International, and African Index Medicus. Two independent authors (J.S.O. & S.E.) reviewed the articles for inclusion, extracted the data, and conducted a quality assessment of the studies. We accepted the World Health Organization definition of catastrophic health expenditures which is out of pocket payments for health care which exceeds 20% of annual house hold income, 10% of household expenditures, or 40% of subsistence expenditures (total household expenditures net food expenditures). Results Of the 1094 articles initially identified, 7 were eligible for inclusion. These were cross-sectional household studies published between 2008 and 2016 in Ghana. They demonstrated that the uninsured paid 1.4 to 10 times more in out-of-pocket payments (OOPs) and were more likely to incur CHEs than the insured. Yet, 6 to 18% of insured households made catastrophic payments for healthcare and all studies reported insured members making OOPs for medicines. Conclusion Evidence suggests that the national health insurance scheme of Ghana over the last 14 years has made some impact on reducing OOPEs, and yet healthcare costs remain catastrophic for a large proportion of insured households in Ghana. Future studies need to explore reasons for the persistence of OOPs for medicines and services that are covered under the scheme.